Problems of the Church Historian - Brooke, Christopher Nugent Lawrence (Studies in church history, 1964)
The members of some newly formed academic societies peer forward into the future with a nice mixture of enthusiasm and uncertainty: enthusiasm for a subject in which they are so fanatically interested that they have dared to found yet another society; uncertainty whether the world at large will admit that the subject exists, whether it will be accorded proper academic respectability. We share, I hope, this enthusiasm; but we have no grounds for uncertainty. It was the study of the Church’s history, from within, which did more than anything else to lay the foundations for the critical study of historical sources, most notably in the work of Mabillon and the Maurists. The study of the Church’s history, and most particularly the history of its founder, rocked the world in the nineteenth century, and played a large part in providing the intellectual grounds both for modern belief and for modern disbelief. The Church’s history has, in the past, provided the locus classicus of the problem of historical bias: is it possible, the question has been asked times out of number, for historians of different persuasions to agree in the study of the early Church, or of the Reformation? The question is a real one; we cannot confidently say more than that they can, without much difficulty, talk the same language; that true scholars nowadays will not think of not talking the same language. And this fact reveals the extraordinary power of reconciliation which the study of the Church’s history has had. It does not always reconcile; the common pursuit of truth did little to foster good relations between Coulton and Gasquet. But this spirit of reconciliation is clearly a feature of our age. It is part of a much larger movement, of which we are all witnesses. I have seen with my own eyes a Jesuit father give a public lecture in Winchester College; I have not seen, but millions of my fellow-countrymen have, Catholic and Anglican metropolitans sitting side by side in cosy amity in a television studio. We all know how limited, in terms of visible reunion, is the significance of these events; but the movement towards reunion among Protestant churches and towards better relations among all the sane branches of the Christian family is one of the striking historical phenomena of our age; and a movement (if I may strike a personal note) of hope and joy. Beyond doubt the study of the Church’s history and the dominance of the historical outlook over the last century and a half have much to do with this.